Acting Intern On-Call Simulations - Norman Benjamin Fredrick (Association of American Medical Colleges, 2012)
Abstract This resource provides instructors with three clinical scenarios for use in a simulation lab. The three cases are intended to be used by fourth-year medical students on their acting internship (subinternship) rotation. The cases all feature inpatient adults with acute undifferentiated complaints. The purpose of the cases is to provide acting interns with a realistic experience of fielding floor calls on their own until backup help arrives. Because the simulations run for only 10 minutes before backup appears, acting interns are placed in a position of having to assess a patient's acute complaints, order tests, and manage the undifferentiated issue. In this capacity, they are challenged to make clinical decisions on their own that have consequences for the patient. Through these experiences, acting interns develop a discomfort with having to make time-pressured patient-management decisions. This discomfort is useful in motivating them to develop personal learning objectives related to assuming increased clinical responsibility of patient care. Students routinely find this to be a valuable experience, albeit uncomfortable. They regularly report that they have never had this kind of experience before and did not realize what it would feel like to be an intern on call. The students also realize the need to begin view medical conditions from a new perspective, namely, that of having to manage patient care. They are forced to step outside the observer role they typically assumed in third year. As an intern on call, they need to know medication names, doses, and routes of administration. For example, they realize that while they may know about atrial fibrillation, they have not paid attention to the management of an acute episode.